RADICAL PARTY SYSTEM CHANGES IN FIVE EAST-CENTRAL EUROPEAN STATES: EUROSCEPTIC AND POPULIST PARTIES ON THE MOVE IN THE 2010s - Ágh, Attila (Baltic Journal of Political Science, 2015)
This paper, in addition to describing the historical trajectory of party systems in the new European Union member states in general, describes the particular cases of five new Eastern-Central European (ECE) member states (NMS-5, the Czech Republic, Hungary, Poland, Slovakia and Slovenia), and the recent emergence of new, second party systems that have recently emerged after the collapse of their first party systems. The main message of this paper is that the historical transformations of the NMS-5 can best be described using a matrix of four party types: 1) populist, 2) Eurosceptic, 3) protest, and 4) extreme-right. Although Eurosceptic parties have been in the forefront of recent analysis, the other three forms included in this matrix are equally important, and even enhance the understanding of Eurosceptic parties in the NMS-5. Like the international literature, the focus of this paper is also on party developments, but includes a complex approach that accounts not only for political, but also for socio-economic, developments in the NMS-5.